Синестетична інтенція словесного образу - Левчук, Тереза Петрівна; Levchuk, Tereza P. (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Fiction differs from other arts because of its universality, encompassed expressive ability of the word, which keeps the original syncretic force. The word always sounds and looks. Verbal image arouses the imagination of the recipient and makes him to draw a picture. The writers are resorting to depictive-expressive opportunities at the level of description, the transfer of mental impressions. However, only in the twentieth century writers understood the synesthetic power of words completely and started to dig down to deep, walled-up in the original mythological consciousness, syncretistic foundations. Modernists have used such ability of words successfully. Synesthesia as the defining principle of the creation of the image is inherent to creativity of Bohdan Ihor Antonych and Vladimir Svidzinsky. Synesthetic intention of verbal images doesn’t just create a unique style of each of these authors, but also witnesses their arhetypal mythological thinking and reveals the ability of intuitive penetration into the depths of the word.

Literatura piękna wśród innych rodzajów sztuki wyróżnia się uniwersalnością, która spowodowana jest wyrażalną możliwością słowa zachowującego pierwotną synkretyczną siłę. Wyraz zawsze brzmi oraz wygląda. Słowny obraz wzbudza wyobraźnie odbiorcy i zmusza go do malowania obrazu. Pisarze wykorzystują przedstawiająco-wyrażające możliwości wyrazów zwłaszcza na poziomie opisu, przekazywania wrażeń psychicznych. I tylko w XX wieku pisarze całkiem uświadomili sobie synestezującą siłę wyrazu i zaczęli poszukiwania podstaw synkretycznych, zawartych w pierwotnej świadomości archetypicznej. Bardzo owocnie posłużyli się taką możliwością słowa moderniści. Synestezja jako podstawa tworzenia obrazu artystycznego występuje w twórczości Bohdana Ihoria Antonycza i Włodzimierza Świdzińskiego. Synestetyczna intencja słownych obrazów nie tylko tworzy niepowtarzalny styl każdego z wymienionych wyżej autorów, ale także decyduje o archetypiczności mitologicznego myślenia pisarzy i ujawnia intuicyjne możliwości przenikania w głąb wyrazu.
Synesthetic intention of verbal image
Keywords: синестезія; інтенція; словесний образ; етимологія; synesthesia; intention; verbal image; etymology; synestezja; intencja; słowny obraz; etymologia